"Kansaamme pirstotaan" : Inkerinsuomalaisten karkotukset ja diaspora Neuvostoliitossa 1930-luvun kirjeissä kuvattuna - Reuter, Anni Maria (Historian Ystavain Liitto, 2021)
I explored the deportations and diaspora of Ingrian Finns from Ingria, area around Leningrad, to different parts of the Soviet Union during the 1930s. Approximately 45, 000 Ingrian Finns were deported during the mass deportations of kulaks and ethnic groups from the frontier zone. Using the concept of diaspora, I analysed 170 private letters sent from Ingria and exile locations (via Ingria) to Finland. Article demonstrated that the concept of diaspora is suitable for describing the experiences of Ingrian Finns living in controlled internal exile in different parts of the country. The forced deportations of Ingrian Finns were traumatic and led to the dispersion of Ingrian Finns to Siberia, Central Asia, the Kola Peninsula, and other peripheries. Ingrian Finns were oriented toward their homeland, kept its memory alive and planned to return. Many escaped there, but runaways could seldom stay permanently. The social status of deportees was low, and they suffered from poverty, illness, loss of rights, and forced hard labour. The mass deaths of Ingrian Finns in different parts of the country reflect both the dispersion and the miserable living conditions. However, Ingrian Finns attempted to preserve their religion, community, identity, culture, and Finnish language. The boundaries with other ethnic and religious groups were clear in the multicultural exile environment, at least in 1930s. The diaspora culture of Ingrian Finns grew in the atmosphere of political, religious, and economical oppression, which made their culture thinner. The Ingrian Finnish social network and community were a crucial part of the diaspora at least until the Great terror (1937–1938), when the correspondence with Finland ceased. Peer reviewed